The application of institutional research in a senior high school of Taiwan - SHUFANG LIN; YIH-JENG LIN (Journal of Advanced Research in Social Sciences and Humanities, 2016)
Aim: To support student recruitment policies and school management strategies with data-driven decisions, the author of this paper conducted an experiment using Institutional Research (IR).Method: In this investigation, the "Qlikview" BI analytical software was used to combine the school management system with the predetermined analysis scenarios. The following four modules were developed based on a review of the relevant literature and the researchers’ firsthand experience: Analysis of enrollment sources; Analysis of student/parent/teacher satisfaction surveys; Analysis of student/teacher progress; Analysis of teacher effectiveness in the classroom.Findings: Figure 5 demonstrates that the analysis outcomes indicate that this IR model can also analyze trends of different students’ enrollment in junior high schools. This senior high school will be able to refocus its efforts on student recruitment once it has a clear picture of the ups and downs in enrollment at various feeder junior highs.Implications/Novel Contribution: Our findings support the adoption of data-driven decision-making and the introduction of novel creative methods into the classroom. Additional research will be required before IR can be widely used in classrooms. This research also helps us understand the possibilities and constraints of IR as a tool for directing institutional management practices in educational institutions.